A safety coating material for lithium-ion battery, a preparation method and application thereof, and a positive electrode sheet for lithium-ion battery

By using a combination of ceramic materials, solid electrolytes, conductive agents, composite adhesives and surfactants in the safety coating of lithium-ion batteries, the problem of insufficient bonding strength of existing lithium-ion batteries is solved, and the safety and electrical performance of the battery is significantly improved.

CN119752230APending Publication Date: 2025-04-04惠州赣锋锂电科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411962890.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The bonding strength of the safety coating of existing lithium-ion batteries is insufficient, which affects the safety and electrical performance of the battery.

Method used

A safety coating material including ceramic materials, solid electrolytes, conductive agents, composite adhesives and surfactants is used to improve the type and proportion of adhesives, and the bonding strength of the safety coating and the electrolyte wetting effect are improved.

Benefits of technology

It significantly improves the safety and electrical performance of lithium-ion batteries, and enhances the battery's performance in room temperature and high temperature circulation, rate charging and discharge, high and low temperature discharge, extrusion, drop, needle puncture, and heavy object impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218857820000071
    Figure BDA0005218857820000071
  • Figure BDA0005218857820000081
    Figure BDA0005218857820000081
Patent Text Reader

Abstract

The present invention provides a safety coating material for lithium-ion batteries, a preparation method and application thereof, and a positive electrode plate for lithium-ion batteries, and belongs to the technical field of lithium-ion batteries. The present invention improves the type and ratio of the binder in the safety coating formula, uses polyvinylidene fluoride and polymethyl methacrylate as a composite binder, and improves the bonding strength (peel strength) and electrolyte infiltration effect of the safety coating of the lithium-ion battery, thereby changing the normal temperature and high temperature cycle, rate charge and discharge, high and low temperature discharge, extrusion, drop, needle puncture, heavy object impact and other performances of the lithium-ion battery. At the same time, it has high mechanical strength, can improve the flexibility of the positive electrode plate, and can fundamentally improve the problem of powder shedding of the safety coating, reduce polarization, and improve the pass rate of safety tests such as needle puncture and heavy object impact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a safety coating material for lithium ion batteries, a preparation method and application thereof, and a positive electrode sheet for lithium ion batteries. Background Art

[0002] At present, the most studied topic in lithium-ion batteries is safety coating, that is, coating the positive electrode current collector with safety coating (ceramic) to improve the safety performance of lithium-ion batteries and prevent thermal runaway. However, the bonding strength (peel strength) of the safety coating will seriously affect the safety performance and basic electrical properties of lithium-ion batteries, such as normal temperature and high temperature cycles, rate charge and discharge, high and low temperature discharge, extrusion, acupuncture, heavy object impact and other performance. Summary of the invention

[0003] The purpose of the present invention is to provide a safety coating material for lithium-ion batteries, a preparation method and application thereof, and a positive electrode plate for lithium-ion batteries, which have high bonding strength and can improve the safety and electrical performance of lithium batteries.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a safety coating material for lithium ion batteries, comprising the following components in parts by weight:

[0006] 5-8 parts of ceramic material, 1-4 parts of solid electrolyte, 0.3-3 parts of conductive agent, 0.2-2 parts of composite binder, 0.1-1 parts of surfactant;

[0007] The composite binder comprises polyvinylidene fluoride and polymethyl methacrylate, and the mass ratio of the polyvinylidene fluoride to the polymethyl methacrylate is 1-10:1-10.

[0008] Preferably, the ceramic material includes one or more of boehmite, aluminum oxide, titanium dioxide, barium titanate and silicon carbide.

[0009] Preferably, the solid electrolyte includes one or more of lithium lanthanum titanate-lithium lanthanum titanate, lithium lanthanum zirconate-lithium lanthanum zirconate and lithium aluminum titanium phosphate.

[0010] Preferably, the conductive agent is a mixture of multi-walled carbon nanotubes and conductive carbon black superp; the mass ratio of the multi-walled carbon nanotubes to the conductive carbon black superp is 1:10.

[0011] Preferably, the surfactant includes at least one of polyether-modified polydimethylsiloxane, alkyl polyoxyethylene ether and polyvinyl pyrrolidone.

[0012] Preferably, the composite adhesive is used in the form of adhesive glue; the preparation method of the adhesive glue comprises:

[0013] The polyvinylidene fluoride and polymethyl methacrylate are mixed with N-methyl pyrrolidone to obtain a binder glue solution; the mixing stirring speed is 500-2400 r / min, and the stirring time is 200-360 min.

[0014] The present invention provides a method for preparing the safety coating material for lithium ion batteries described in the above technical solution, comprising the following steps:

[0015] The ceramic material, the solid electrolyte, the conductive agent, the composite binder and the surfactant are mixed to obtain the safety coating material for the lithium ion battery.

[0016] The present invention provides the application of the safety coating material for lithium ion batteries described in the above technical solution or the safety coating material for lithium ion batteries prepared by the preparation method described in the above technical solution in lithium ion batteries.

[0017] The present invention provides a positive electrode plate for a lithium ion battery, comprising a safety coating, a positive electrode active material and a positive electrode current collector, wherein the positive electrode current collector is coated with the safety coating on both sides, and the positive electrode active material is coated on each side of the safety coating; the safety coating is formed by the safety coating material for lithium ion batteries described in the above technical solution.

[0018] Preferably, the thickness of each safety coating is independently 1 to 10 μm.

[0019] The present invention provides a safety coating material for lithium-ion batteries. By improving the type and ratio of the binder in the safety coating formula, polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA) are used as composite binders to enhance the bonding strength (peel strength) and electrolyte infiltration effect of the lithium-ion battery safety coating, thereby changing the performance of the lithium-ion battery in normal temperature and high temperature cycling, rate charge and discharge, high and low temperature discharge, extrusion, drop, needle puncture, heavy object impact, etc.

[0020] The present invention adds a conductive agent to the safety coating to improve the electronic conductivity, reduce the contact resistance of the electrode, accelerate the movement rate of the electrons, and ensure that the pole piece has good charge and discharge performance; the present invention adopts a specific number of composite conductive agents to reduce the resistance of the pole piece, thereby ensuring that the lithium-ion battery has excellent room temperature and high temperature cycle, rate charge and discharge, high and low temperature discharge, high temperature storage, acupuncture, and heavy object impact performance. The present invention uses ceramic materials to absorb part of the heat generated by thermal runaway to improve the puncture pass rate of the lithium-ion battery; and when the battery is squeezed and the positive and negative pole pieces are easy to contact, the safety coating is conducive to wrapping and protecting the pole piece to avoid thermal runaway of the battery due to short circuit; at the same time, solid electrolytes are used to ensure good thermal stability.

[0021] The safety coating material of the present invention can improve the flexibility and overall mechanical strength of the positive electrode plate, and can fundamentally improve the problem of safety coating powder shedding, reduce polarization, and improve the pass rate of safety tests such as needle puncture and heavy object impact. DETAILED DESCRIPTION

[0022] In the present invention, unless otherwise specified, the raw materials or reagents used are commercially available products well known in the art.

[0023] The present invention provides a safety coating material for lithium ion batteries, comprising the following components in parts by weight:

[0024] 5-8 parts of ceramic material, 1-4 parts of solid electrolyte, 0.3-3 parts of conductive agent, 0.2-2 parts of composite binder, 0.1-1 parts of surfactant;

[0025] The composite binder comprises polyvinylidene fluoride and polymethyl methacrylate, and the mass ratio of the polyvinylidene fluoride to the polymethyl methacrylate is 1-10:1-10.

[0026] In terms of mass fraction, the safety coating material for lithium-ion batteries provided by the present invention includes 5 to 8 parts of ceramic material, and more preferably 6 to 7 parts. In the present invention, the ceramic material preferably includes one or more of boehmite, aluminum oxide, titanium dioxide, barium titanate and silicon carbide; when the ceramic material is two or more of the above, the present invention has no special restrictions on the ratio of different types of ceramic materials, and any ratio is acceptable. The present invention has no special restrictions on the specific specifications and sources of the ceramic material, and commercially available products known in the art can be used.

[0027] Based on the mass fraction of the ceramic material, the safety coating material for lithium ion batteries provided by the present invention includes 1 to 4 parts of a solid electrolyte, more preferably 2 to 3 parts, and the solid electrolyte preferably includes one or more of lithium lanthanum titanyl-lithium lanthanum titanate, lithium lanthanum zirconyl-lithium lanthanum zirconate and lithium aluminum titanium phosphate; when the solid electrolyte is more than two of the above, the present invention has no special limitation on the ratio of different types of solid electrolytes, and any ratio is acceptable.

[0028] The present invention has no particular limitation on the sources of the lithium lanthanum titanyl-lithium lanthanum titanate and lithium lanthanum zirconyl-lithium lanthanum zirconate, and any commercially available product known in the art may be used.

[0029] Based on the mass fraction of the ceramic material, the safety coating material for lithium ion batteries provided by the present invention includes 0.3 to 3 parts of a conductive agent, more preferably 0.5 to 2 parts, and further preferably 1 to 1.5 parts. The conductive agent is preferably a mixture of multi-walled carbon nanotubes and conductive carbon black superp; the mass ratio of the multi-walled carbon nanotubes to the conductive carbon black superp is preferably 1:10.

[0030] Based on the mass fraction of the ceramic material, the safety coating material for lithium ion batteries provided by the present invention includes 0.2 to 2 parts of a composite binder, more preferably 0.5 to 1.5 parts, and further preferably 1 part; the composite binder includes polyvinylidene fluoride and polymethyl methacrylate, and the mass ratio of polyvinylidene fluoride to polymethyl methacrylate is 1 to 10:1 to 10.

[0031] In the present invention, the composite adhesive is preferably used in the form of an adhesive glue solution; the preparation method of the adhesive glue solution comprises:

[0032] The polyvinylidene fluoride and polymethyl methacrylate are mixed with N-methylpyrrolidone (NMP) to obtain a binder glue solution. In the present invention, NMP is preferably used to prepare polyvinylidene fluoride and polymethyl methacrylate into polyvinylidene fluoride glue solution with a solid content of 8% and polymethyl methacrylate glue solution with a solid content of 6%.

[0033] In the present invention, the stirring speed of the mixing is preferably 500 to 2400 r / min, more preferably 2000 r / min, and the stirring time is preferably 200 to 360 min, further preferably 240 min.

[0034] Based on the mass fraction of the ceramic material, the safety coating material for lithium ion batteries provided by the present invention includes 0.1 to 1 parts of surfactant, more preferably 0.3 to 0.8 parts, and further preferably 0.5 to 0.6 parts; the surfactant preferably includes at least one of polyether-modified polydimethylsiloxane, alkyl polyoxyethylene ether and polyvinyl pyrrolidone. When the surfactant is two or more of the above, the present invention has no special limitation on the ratio of different types of surfactants, and can be adjusted according to actual needs.

[0035] The present invention provides a method for preparing the safety coating material for lithium ion batteries described in the above technical solution, comprising the following steps:

[0036] The ceramic material, the solid electrolyte, the conductive agent, the composite binder and the surfactant are mixed to obtain the safety coating material for the lithium ion battery.

[0037] The present invention has no special limitation on the mixing of the ceramic material, solid electrolyte, conductive agent, composite binder and surfactant. The materials can be mixed evenly according to a process well known in the art.

[0038] The present invention provides the application of the safety coating material for lithium ion batteries described in the above technical solution or the safety coating material for lithium ion batteries prepared by the preparation method described in the above technical solution in lithium ion batteries.

[0039] The present invention provides a positive electrode plate for a lithium ion battery, comprising a safety coating, a positive electrode active material and a positive electrode current collector, wherein the positive electrode current collector is coated with the safety coating on both sides, and the positive electrode active material is coated on each side of the safety coating; the safety coating is formed by the safety coating material for lithium ion batteries described in the above technical solution.

[0040] The present invention has no special limitation on the positive electrode active material and the positive electrode current collector, and the corresponding materials known in the art can be used. The positive electrode active material is more preferably lithium cobalt oxide, lithium iron phosphate or lithium manganese oxide.

[0041] In the present invention, the thickness of each safety coating layer is preferably independently 1 to 10 μm.

[0042] In the present invention, the safety coating is preferably prepared by mixing a binder glue with a ceramic material, a solid electrolyte and a conductive agent to obtain a safety coating slurry, and applying the slurry to the positive electrode current collector to form a safety coating.

[0043] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] Example 1

[0045] The safety coating material provided in this embodiment includes the following components in parts by weight:

[0046] 8 parts of boehmite, 2 parts of solid electrolyte, 0.5 parts of conductive agent, 1 part of composite binder, 0.1 parts of surfactant;

[0047] Wherein, the composite binder is polyvinylidene fluoride and polymethyl methacrylate; the mass ratio of polyvinylidene fluoride to polymethyl methacrylate is 9:1;

[0048] Among them, the solid electrolyte is lithium aluminum titanium phosphate (Zhejiang Fengli New Energy Technology Co., Ltd.), the conductive agent is multi-walled carbon nanotubes and conductive carbon black superp with a mass ratio of 1:10, and the surfactant is polyether modified polydimethylsiloxane (BYK Chemical).

[0049] Example 2

[0050] The safety coating material provided in this embodiment includes the following components in parts by weight:

[0051] 8 parts of boehmite, 2 parts of solid electrolyte, 0.5 parts of conductive agent, 1 part of composite binder, 0.1 parts of surfactant;

[0052] The composite binder is polyvinylidene fluoride and polymethyl methacrylate; the mass ratio of polyvinylidene fluoride to polymethyl methacrylate is 5:5;

[0053] Wherein, the solid electrolyte, conductive agent and surfactant are the same as those in Example 1.

[0054] Example 3

[0055] The safety coating material provided in this embodiment includes the following components in parts by weight:

[0056] 8 parts of boehmite, 2 parts of solid electrolyte, 0.5 parts of conductive agent, 1 part of composite binder, 0.1 parts of surfactant;

[0057] The composite binder is polyvinylidene fluoride and polymethyl methacrylate; the mass ratio of polyvinylidene fluoride to polymethyl methacrylate is 1:9;

[0058] Wherein, the solid electrolyte, conductive agent and surfactant are the same as those in Example 1.

[0059] Application Example 1

[0060] A positive electrode sheet comprises a safety coating, a positive electrode active material and a current collector. The safety coating slurry is coated on both sides of the positive electrode current collector to form a safety coating with a thickness of 3 μm. The positive electrode active material is then coated on the safety coating to form a positive electrode sheet.

[0061] The positive electrode current collector is aluminum foil with a thickness of 4 to 20 μm and a tensile strength of 180 to 380 MPa;

[0062] The positive electrode active material is lithium cobalt oxide;

[0063] Safety coating slurry: Polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA) are mixed with N-methylpyrrolidone according to the dosage ratio in Example 1 to prepare polyvinylidene fluoride glue with a solid content of 8% and polymethyl methacrylate glue with a solid content of 6%, respectively. The obtained polyvinylidene fluoride glue and polymethyl methacrylate glue are stirred and mixed at a stirring speed of 2000 r / min for 240 min, and mixed with the ceramic material, solid electrolyte, conductive agent and surfactant in Example 1 to obtain a safety coating slurry.

[0064] Application Example 2

[0065] The only difference from Application Example 1 is that the safety coating material in Example 2 is used.

[0066] Application Example 3

[0067] The only difference from Application Example 1 is that the safety coating material in Example 3 is used.

[0068] Comparative application example 1

[0069] The only difference from Application Example 1 is that the binder in the safety coating slurry is only polyvinylidene fluoride (PVDF); the rest is the same as Application Example 1.

[0070] Test Case

[0071] The positive electrode sheets and negative electrode (artificial graphite), diaphragm (PE diaphragm), and electrolyte (4.5V fast-charge electrolyte, Shenzhen Xinzhoubang Technology Co., Ltd.) in Application Examples 1 to 3 and Comparative Application Example 1 were assembled into soft-pack lithium-ion batteries, and the batteries were charged and tested.

[0072] Performance Test:

[0073] The test capacity is 5Ah. The safety tests are all 0.5C constant current and constant voltage charging to 4.5V, with a cut-off current of 0.02C. The cycle charge and discharge rate is 1.5C step charging and 1C discharge. The results are shown in Table 1.

[0074] Table 1 Test data of application examples 1 to 3 and comparative application example 1

[0075]

[0076]

[0077] As can be seen from Table 1, the safety coating material formed by the composite binder (polyvinylidene fluoride PVDF and polymethyl methacrylate PMMA) of the present invention can improve the performance of peeling strength, compaction density, needle puncture, heavy object impact, extrusion, bending and unfolding, and circulation, that is, the safety and electrical performance of the battery are improved, which shows that the present invention has obvious advantages over the prior art.

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A safety coating material for lithium ion batteries, characterized in that: The composition includes the following components in parts by weight: 5-8 parts of ceramic material, 1-4 parts of solid electrolyte, 0.3-3 parts of conductive agent, 0.2-2 parts of composite binder, 0.1-1 parts of surfactant; The composite binder comprises polyvinylidene fluoride and polymethyl methacrylate, and the mass ratio of the polyvinylidene fluoride to the polymethyl methacrylate is 1-10:1-10.

2. The safety coating material for lithium ion batteries according to claim 1, characterized in that: The ceramic material includes one or more of boehmite, aluminum oxide, titanium dioxide, barium titanate and silicon carbide.

3. The safety coating material for lithium ion batteries according to claim 1, characterized in that: The solid electrolyte includes one or more of lithium lanthanum titanate-lithium lanthanum titanate, lithium lanthanum zirconate-lithium lanthanum zirconate and lithium aluminum titanium phosphate.

4. The safety coating material for lithium ion batteries according to claim 1, characterized in that: The conductive agent is a mixture of multi-walled carbon nanotubes and conductive carbon black superp; the mass ratio of the multi-walled carbon nanotubes to the conductive carbon black superp is 1:

10.

5. The safety coating material for lithium ion batteries according to claim 1, characterized in that: The surfactant includes at least one of polyether-modified polydimethylsiloxane, alkyl polyoxyethylene ether and polyvinyl pyrrolidone.

6. The safety coating material for lithium ion batteries according to claim 1, characterized in that: The composite adhesive is used in the form of adhesive glue; The preparation method of the adhesive glue comprises: Mixing polyvinylidene fluoride and polymethyl methacrylate with N-methylpyrrolidone to obtain a binder glue solution; The mixing speed is 500-2400 r / min, and the mixing time is 200-360 min.

7. The method for preparing the safety coating material for lithium ion batteries according to any one of claims 1 to 6, characterized in that: The following steps are involved: The ceramic material, the solid electrolyte, the conductive agent, the composite binder and the surfactant are mixed to obtain the safety coating material for the lithium ion battery.

8. Use of the safety coating material for lithium ion batteries according to any one of claims 1 to 6 or the safety coating material for lithium ion batteries prepared by the preparation method according to claim 7 in lithium ion batteries.

9. A positive electrode plate for a lithium-ion battery, characterized in that: It comprises a safety coating, a positive electrode active material and a positive electrode current collector, wherein the positive electrode current collector is coated with the safety coating on both sides, and the positive electrode active material is coated on each side of the safety coating; the safety coating is formed by the safety coating material for lithium ion battery according to any one of claims 1 to 6.

10. The positive electrode plate of a lithium-ion battery according to claim 9, characterized in that: The thickness of the safety coating on each side is independently 1 to 10 μm.

Citation Information

Cited By

  • A ptc safety coating and its preparation method and application

    CN122502957A